2002
DOI: 10.4049/jimmunol.169.11.6316
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Cutaneous Immune Response to Experimental Haemophilus ducreyi Infection and Its Relevance to HIV-1 Acquisition

Abstract: Haemophilus ducreyi causes the sexually transmitted disease chancroid, which facilitates HIV-1 transmission. Skin biopsies were obtained from subjects experimentally infected with H. ducreyi to study the evolution of the immune response and immunophenotypes relevant to transmission of HIV-1. Compared with peripheral blood, there was an enrichment of T cells and macrophages after 48 h of infection in the skin. Neutrophils became the predominant cell type by 7–9 days. By immunohistochemistry, macrophage-inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…It is likely that in vitro hyperactivation overcame the differences that existed in CCR5 promoter activity before stimulation with the mitogen, and infectivity levels in the two groups were therefore equal. This finding also emphasizes the possibility that relative resistance to infection conferred by specific CCR5 genotype combinations can be overcome by cellular activation, as may be the case during sexually transmitted disease-triggered mucosal inflammation (15,32,42,47).…”
Section: Discussionmentioning
confidence: 67%
“…It is likely that in vitro hyperactivation overcame the differences that existed in CCR5 promoter activity before stimulation with the mitogen, and infectivity levels in the two groups were therefore equal. This finding also emphasizes the possibility that relative resistance to infection conferred by specific CCR5 genotype combinations can be overcome by cellular activation, as may be the case during sexually transmitted disease-triggered mucosal inflammation (15,32,42,47).…”
Section: Discussionmentioning
confidence: 67%
“…Neutrophils are the predominant cell type in pustules (19). Phagocytosis of apoptotic neutrophils by macrophages promotes M2 polarization and the resolution of inflammation (14).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are rapidly recruited to H. ducreyi-infected skin in human inoculation experiments (19,37). To determine the expression of surface markers associated with M1 and M2 polarization of macrophages, biopsy specimens of pustules and PBMC obtained from 10 participants who were experimentally infected were analyzed by flow cytometry.…”
Section: Phenotypic Characterization Of Macrophages In Pustulesmentioning
confidence: 99%
“…There is a limited amount of information about T cells that home to skin in response to infection (23,28,32). Human inoculation experiments with H. ducreyi provide a unique opportunity to study the trafficking and phenotypes of T cells recruited chiefly to the dermis in response to this pathogen (20,32). Previous work in our laboratory showed that CD4 cells isolated from H. ducreyi-infected pustules are memory cells that are enriched for the skin-homing markers CLA and CCR4.…”
mentioning
confidence: 99%
“…The lesion consists of a polymorphonuclear leukocyte infiltrate that forms an epidermal abscess and a deep dermal perivascular infiltrate of T cells and macrophages that resembles a poorly formed granuloma that extends interstitially to just below the epidermis (26,36). By 48 h of infection, T cells make up about 50% of the leukocyte infiltrate and remain abundant throughout the course of experimental infection (20).…”
mentioning
confidence: 99%